Depression screening in primary care in the Republic of Trinidad and Tobago - Ali, Sherese (2017)
ABSTRACT: The World Health Organization (WHO) predicts that unipolar depression will be the second leading cause of disability in the world by the year 2020. Amongst their many recommendations to address this problem are mental health training in primary health care and the integration of mental health into primary care. Identified areas of policy development such as health promotion and case detection at this level would necessarily entail adequate education and screening at a primary care level. The study sought to investigate the rate of routine screening for depression in clinical practice, and the attitudes towards mental health amongst primary health care physicians in Trinidad and Tobago using a physician attitude survey. It used an observational, single blind design. The principal investigator administered an independent screen for depression on all patients to determine the base rate of positive depression screen. Data and statistical analyses were stratified based on patient gender, individual physician and clinic site. Six clinic sites within 1 regional health authority in the island were sampled. 119 patients and 11 primary health care physicians participated. Of the 119 patients 29 had a positive screen for depression based on a PHQ-2 administered by the investigator. The depression screening rate (fraction of patients routinely screened by the physician), and therefore their detection rate (number screened positive by the physician, divided by the total number of positive screens according the PHQ-2) were very low, 9/119 (7.6%) and 2/29 (6.9%), respectively. The only significant correlation with screening by primary care physicians was by clinic site. Overall physicians demonstrated a positive attitude towards mental health and 10/11 physicians felt they needed more training in mental health. The small sample size and restriction to one regional health authority limits generalizability of the findings. Nevertheless, the depression screening rate reflects those in similar studies in both developing and developed countries.